1999
DOI: 10.1111/j.1539-6924.1999.tb00435.x
|View full text |Cite
|
Sign up to set email alerts
|

“How Exposed Is Exposed Enough?” Lay Inferences About Chemical Exposure

Abstract: The concept of exposure is central to chemical risk assessment and plays an important role in communicating to the public about the potential health risks of chemicals. Research on chemical risk perception has found some indication that the model lay people use to judge chemical exposure differs from that of toxicologists, thereby leading to different conclusions about chemical safety. This paper presents the results of a series of studies directed toward developing a model for understanding how lay people int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 9 publications
1
42
1
3
Order By: Relevance
“…It seems then that it is at the point of human judgment and application that the riskassessment enterprise is vulnerable, as both experts and laypeople have been found to make the 912 CRIMINAL JUSTICE AND BEHAVIOR same cognitive errors (MacGregor, Slovic, & Malmfors, 1999;Nisbett & Ross, 1980;Slovic et al, 1982). One of these errors is the ignoring of base rate information when perceiving risk.…”
Section: The Communication and Perception Of Riskmentioning
confidence: 99%
“…It seems then that it is at the point of human judgment and application that the riskassessment enterprise is vulnerable, as both experts and laypeople have been found to make the 912 CRIMINAL JUSTICE AND BEHAVIOR same cognitive errors (MacGregor, Slovic, & Malmfors, 1999;Nisbett & Ross, 1980;Slovic et al, 1982). One of these errors is the ignoring of base rate information when perceiving risk.…”
Section: The Communication and Perception Of Riskmentioning
confidence: 99%
“…Public attitudes about fire and fire management, including activities that have an impact on fire management such as the use of prescribed fire for fuels management, can exert powerful effects on how organizations frame problems and set priorities for fire management actions. For example, the precautionary principle as applied to risk management decisionmaking is generally reflective of a broad public attitude that favors a conservative interpretation of risk and that corresponds to a generally risk-averse public attitude with respect to outcomes that are perceived as severe or catastrophic (e.g., Graham 2001, MacGregor et al 1999, Sandin 1999, Slovic 2000. In essence, the precautionary principle is a "better safe than sorry" view that prescribes protective action even when no harm is certain to occur.…”
Section: Societal Metadecisionsmentioning
confidence: 99%
“…We have no empirical results to date that indicate how much the public is aware of the use of nuclear materials in space research, or how they would see themselves as exposed to possible risks if their awareness increased. Previous research has shown that people's perceptions of exposure to hazards, such as chemicals, can be highly sensitive to the way in which information is presented to them, and that even very small amounts of exposure to materials believed to be hazardous can lead to inferences of great harm (MacGregor, Slovic, & Malmfors, 1999).…”
Section: Nuclear Materials In Space Nuclear Materials In Spacementioning
confidence: 99%
“…In the context of chemical risks, even relatively simple concepts such as "exposure" can have a multiplicity of meanings to non-scientists (MacGregor, Slovic, & Malmfors, 1999).…”
Section: Evaluations Of Media Expressions Of Radiation Risksmentioning
confidence: 99%
See 1 more Smart Citation